Ageing shocks and short-run regional labour market dynamics in a spatial panel VAR approach. Issue 8 (13th February 2018) - Mitze, Timo; Schmidt, Torben Dall; Rauhut, Daniel; Kangasharju, Aki
ABSTRACT: Using a flexible spatial panel VAR model for a small-scale labour market system, we investigate the dynamic interdependences between changes in the demographic structure and the labour market performance of a regional economy. With a particular focus on ageing shocks, we describe an increase in the share of elderly in regional population due to exogenous changes in the institutional context, such as pension reforms. The regional labour market implications of an ageing shock are then tested with regard to the effects on employment growth, unemployment and labour participation rate. Our results based on a sample of 71 Scandinavian regions point to negative regional labour market effects of an ageing shock implying a reduction in employment growth and a temporarily declining labour participation rate, while the unemployment rate increases. Importantly, spatial spillovers amplify these negative impacts through a marginalization of macro-regional labour markets. As a robustness check, we reverse the causal ordering and analyze the responses to a positive macroeconomic shock which initially increases employment growth. We find direct and spatially indirect adjustment patterns characterized by a reduction of the unemployment rate, an increase in the labour participation rate and a decrease in the share of elderly in the population.